Incidence of choroidal neovascularization in the fellow eye in the comparison of age-related macular degeneration treatments trials - Maguire, Maureen G; Daniel, Ebenezer; Shah, Ankoor R; Grunwald, Juan E; Hagstrom, Stephanie A; Avery, Robert L; Huang, Jiayan; Martin, Revell W; Roth, Daniel B; Castellarin, Alessandro A; Bakri, Sophie J; Fine, Stuart L; et al. (Ophthalmology (Rochester, Minn.), 2013)
To assess the influence of drug; dosing regimen; and traditional, nontraditional, and genetic risk factors on the incidence of choroidal neovascularization (CNV) in the fellow eye of patients treated for CNV with ranibizumab or bevacizumab. Cohort study of patients enrolled in a multicenter, randomized clinical trial. Patients with no CNV in the fellow eye at the time of enrollment in the Comparison of Age-Related Macular Degeneration Treatments Trials (CATT). Eligibility criteria for the clinical trial required that study eyes have evidence on fluorescein angiography and optical coherence tomography of CNV secondary to age-related macular degeneration (AMD) and visual acuity between 20/25 and 20/320. Treatment for the study eye was assigned randomly to either ranibizumab or bevacizumab and to 3 different regimens for dosing over a 2-year period. The genotypes for 4 single nucleotide polymorphisms (SNPs) associated with risk of AMD were determined. Only patients without CNV in the fellow eye at baseline were considered at risk. The CATT ophthalmologists examined patients every 4 weeks through 2 years and recorded treatment for CNV in the fellow eye. Development of CNV in the fellow eye. Among 1185 CATT participants, 727 (61%) had no CNV in the fellow eye at enrollment. At 2 years, CNV had developed in 75 (20.6%) of 365 patients treated with ranibizumab and in 60 (16.6%) of 362 patients treated with bevacizumab (absolute difference, 4.0%; 95% confidence interval [CI], -1.7% to 9.6%; P = 0.17). The risk ratio for pro re nata dosing relative to monthly dosing was 1.1 (95% CI, 0.8-1.6). Greater elevation of the retinal pigment epithelium and fluid in the foveal center of the study eye were associated with increased incidence of CNV in the fellow eye. Incidence was not associated with genotype on rs1061170 (CFH), rs10490924 (ARMS2), rs11200638 (HTRA1), and rs2230199 (C3; P>0.35). Through 2 years, there was no statistically significant difference between ranibizumab and bevacizumab in incidence of CNV in the fellow eye. Genotype on 4 SNPs previously found to be associated with AMD did not affect the risk of CNV in the fellow eye among CATT patients. Proprietary or commercial disclosure may be found after the references.